Using routine data for long term impact evaluation: Methodological reflections from a complex health system intervention in a low-income context - Naasegnibe Kuunibe (Cogent Public Health, 2023)
Abstract: There is increased availability of routine secondary data globally in many health facilities due to technological advancement and the growth in electronic records. Such data present the opportunity for their use when evaluating health system intervention programs. Unfortunately, the progress is rather slow as many researchers and development partners rely on survey data with the associated costs and inconveniences. Admittedly, using routine secondary data for impact evaluation can be tedious. There is a need for a step-by-step guide for early career researchers who may be interested in such an approach. This paper provides a methodological reflection based on a graduate study experience. It highlights the necessary methodological concepts and exemplifies the same using sample results. Hopefully, the study will guide early career researchers desiring to carry out similar studies to think through each step deeply and consciously carefully. It is intended as a methodological guide rather than an empirical work.